(3x-1)^3^ = exponents, so it's (3x-1) cubed

1 Answer | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

You did not specify what is the required information.

I assume that you either need to expand or find the roots.

First, let us expand between brackets using the formula:

We know that:

`(a-b)^3 = a^3 - 3a^2 b +3ab^2 - b^3`

`==> (3x-1)^3 = 27x^3 -27x^2 +9x -1`

`` If you need to determine the roots ( zeros):

==> `(3x-1)^3 = 0`

`==> 3x-1 = 0`

`==> 3x = 1`

`==> x = 1/3`

``

We’ve answered 318,994 questions. We can answer yours, too.

Ask a question